The Influence of the Marketing Mix on Consumer Purchase Interest in the Harapan Abadi Store Business Gowa Regency - Nur Amin (Yayasan Amerta Insan Unggul, 2023)
The study aimed to assess the impact of product, price, distribution, and promotion on consumer purchasing interest at Harapan Abadi stores in Gowa Regency. The research population comprised visitors to the Harapan Abadi store in Gowa Regency, with a sample size of 80 respondents selected using a sampling technique. Data was collected through questionnaires, and multiple linear regression analysis was employed for data analysis. The findings revealed that the product and price variables had an insignificant negative effect on purchase intention. This suggests that neither product quality nor pricing significantly influenced consumer buying interest at the Harapan Abadi store in Gowa Regency. Conversely, the distribution and promotion variables exhibited a positive and significant impact on purchase intention. This indicates that improved product distribution and promotional activities led to a notable increase in consumer buying interest at Harapan Abadi stores in Gowa Regency. Based on these results, recommendations for businesses in Gowa Regency include prioritizing product quality, ensuring competitive pricing, enhancing promotional efforts, and optimizing distribution channels to facilitate smooth sales and attract consumers. By focusing on these factors, businesses can better meet consumer demands and enhance their competitiveness in the market. In conclusion, this research sheds light on the factors influencing consumer purchasing interest at Harapan Abadi stores in Gowa Regency, highlighting the importance of effective distribution and promotion strategies in driving consumer buying behavior.